Eliotic Seeds in B. S. Al Sayyab's Poem "The Rain Song'': An Analytical Study - Ahmed Taher Abdu Nagi (Taez University, 2020)
"The Rain Song" is considered one of the most notable poems of modern Arabic poetry in general and of B. S. Al Sayyab in particular. It is a landmark in the history of modern Arabic poetry. The present paper aims at unearthing the seeds of T. S. Eliot in Al Sayyab's poem ''The Rain Song''. Eliot is a literary figure who reshaped the literary scene not only in England, but also in the world. Accordingly, the present paper has ploughed the soil of the poem ''The Rain Song'' to discover some scattered Eliotic seeds. Modernism affected Arabic poetry early in the first half of the twentieth century. As a translator and a poet, Al Sayyab is able to delve into English poetry which becomes a catalyst that has infused him to modernize the Arabic poem. Unmistakably, Al Sayyab does not copy the Eliotic techniques of modernism. He has blended them to create something new and creative based upon the Arabic heritage. This study concludes that the free verse, mythical, imagist, symbolic, and allusive methods are the Eliotic seeds implanted in ''The Rain Song''. Such new techniques were not used in the classical Arabic poetry. Some examples of these seeds and fingerprints, in ''The Rain Song'', are presented in this study.